The mermaid in two Andean and Amazonian oral stories - Cornejo Chaparro, Manuel (2021)
In this article we will analyze two stories about the mermaid in Andean and Amazonian cultural contexts. We will emphasize both their discursive similarities and differences. Through the analysis of these stories, we propose a cultural interaction between the Andean and Amazonian societies and outline some notions about the dynamic process of oral literatures.